2015
DOI: 10.4049/jimmunol.1303179
|View full text |Cite
|
Sign up to set email alerts
|

A CD46-like Molecule Functional in Teleost Fish Represents an Ancestral Form of Membrane-Bound Regulators of Complement Activation

Abstract: In the complement system, the regulators of complement activation (RCA) play crucial roles in controlling excessive complement activation and in protecting host cell from misdirected attack of complement. Several members of RCA family have been cloned from cyclostome and bony fish species and classified into soluble and membrane-bound type as in mammalian RCA factors. Complement-regulatory functions have been described only for soluble RCA of lamprey and barred sand bass; however, little is known on the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…These are composed of approximately 60 amino acids of which 10–18 are highly conserved, as well as four invariant cysteines that define the CCP architecture (a loop within a loop structure) . The genomic organization and clustering of RCA genes are diverse among species that include mice, chicken, frog, and teleost (the most common group of ray‐finned bony fish [reviewed in ]). Both phylogenetic and genomic evidence indicates the emergence of the RCA by the time of cyclostomes (the most ancient class of vertebrates).…”
Section: Cell Membranementioning
confidence: 99%
See 1 more Smart Citation
“…These are composed of approximately 60 amino acids of which 10–18 are highly conserved, as well as four invariant cysteines that define the CCP architecture (a loop within a loop structure) . The genomic organization and clustering of RCA genes are diverse among species that include mice, chicken, frog, and teleost (the most common group of ray‐finned bony fish [reviewed in ]). Both phylogenetic and genomic evidence indicates the emergence of the RCA by the time of cyclostomes (the most ancient class of vertebrates).…”
Section: Cell Membranementioning
confidence: 99%
“…Both phylogenetic and genomic evidence indicates the emergence of the RCA by the time of cyclostomes (the most ancient class of vertebrates). A CD46‐like molecule has been identified and characterized in bony fish . Moreover, genes containing the complement control protein (CCP) domains common to human complement regulatory elements have been identified as early as in ascidians …”
Section: Cell Membranementioning
confidence: 99%
“…Complement systems similar to that in mammals also have been identified in birds, fish, amphibians, and reptiles. An AP is also found in more primitive species, even those lacking a circulatory system [13]. The complement system consists of three major activating pathways that are independently triggered, yet all have the common goal of modifying the target membrane by depositing C3 activation products and then engaging a common terminal membrane-attack complex (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These are separated by a 14–59 cM segment that includes a number of genes unrelated to complement [21]. Complement regulatory genes share a common ancestral motif from which they arose by multiple gene duplication events [13, 19, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three membrane-bound complement regulatory protein isoforms gTecrem-1, gTecrem-2 and gTecrem-3 were identified in ginbuna crucian carp (Carassius auratus langsdorfii) (Nur et al, 2013). A CD46-like complement-regulatory membrane protein (cTecrem), an ortholog of a zebrafish RCA group 2 gene ZRC1, was cloned and characterized in common carp (Tsujikura et al, 2015). In channel catfish (Ictalurus punctatus), the primary aquaculture species in the United States, complement factors Bf/C2 and Df , and three complement regulatory protein genes, CD59, factor I, and C1INH have been reported (Abernathy et al, 2009;Yeh and Klesius, 2007), and C1INH was found to be significantly up-regulated at early stages after bacterial infection with Edwardsiella ictaluri .…”
Section: Introductionmentioning
confidence: 99%